MICROFINANCE TO MICROENTERPRISES: A STUDY - Rao, Raghavendra; Salian, Ramesh (International Journal For Research In Business, Management And Accounting, 2020)
A sound financial system backed by strong banking sector is a pre-requisite for overall economic development and financial stability. No doubt, banking industry and banking services have expanded. However, the problem of exclusion continued even after social control of banks. In the midst of the apparent inadequacies to cater to the financial requirements of the poor, an innovation in the credit delivery system named Self-Help Groups emerged. This paper attempts to study potential and performance of SHGs in promoting selfemployment among the SHG members and to understand its impact on income and employment. Microfinance is not an end in itself. SHGs are a strategic instrument to eradicate poverty and to realise the objective of economic development and empowerment of the poor. Microfinance in one stroke cannot transform the livelihood of the people. The data compiled clearly indicates positive impact of SHG lending on income and employment and a move towards self-employment development. The challenges confronted with the SHGs in moving towards self-employment are both internal and external in nature. Microcredit can effectively work and promote further success, only when it works only when loan offered directed is productively utilised. There is the need for creating awareness among the rural folk about the rational use of funds borrowed. Mentoring is the need of the hour.